Assessment of orthopedist exposure to occupational doses of radiation in foot and ankle surgeries - Zigovski, Thiago Pavani; Endlich, Larissa Lopes; Sato, Aleksei Dickow; Filipov, Danielle; Corrêa, Janine Nicolosi (Scientific Journal of the Foot & Ankle, 2019)
Objective: To measure the doses of occupational radiation to which a physician who performs orthopedic surgery of the foot and ankle using a fluoroscopy device is exposed during work and to compare those doses with the values provided in the current legislation and propose measures of radioprotection. Methods: Thermoluminescent dosimetry (TLD) was used to measure radiation in critical target areas (whole-body, lens, thyroid, right and left hands) of the surgeon’s body during all the surgical procedures performed by him between 12/19/2017 and 2/5/2018. From the mean dose values obtained for the procedures, the dose of annual radiation exposure was estimated for each of the regions analyzed and compared with the current legislation. Results: The estimate of the annual radiation dose received by the surgeon to the chest region, above the lead apron, was 5 times higher than that established by the national legislation. However, considering the use of the lead apron, the dose was acceptable. Estimates of equivalent doses for the limbs and thyroid had results within the levels required by the current legislation. The equivalent dose for the lens, on the other hand, was 4 times higher than that established by the legislation. Conclusion: During the workday, the foot and ankle orthopedic surgeon is exposed to doses of radiation higher than those considered acceptable. The data corroborate the need to wear radiological protective clothing, especially a lead apron and goggles. Level of Evidence IV; Prognostic Study; Case Series.